2010
DOI: 10.1007/s00248-010-9715-5
|View full text |Cite
|
Sign up to set email alerts
|

Social Amoebae: Environmental Factors Influencing Their Distribution and Diversity Across South-Western Europe

Abstract: The social amoebae (dictyostelids) are the only truly multicellular lineage within the superkingdom Amoebozoa, the sister group to Ophistokonts (Metazoa+Fungi). Despite the exceptional phylogenetic and evolutionary value of this taxon, the environmental factors that determine their distribution and diversity are largely unknown. We have applied statistical modeling to a set of data obtained from an extensive and detailed survey in the south-western of Europe (The Iberian Peninsula including Spain and Portugal)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…However, if there is a corresponding increase in the genetic diversity within a particular amoeba species as pH approaches neutral, then because amoeba samples were collected by pooling multiple individual fruiting bodies, these more genetically diverse amoebae may carry different bacteria leading to an increase in alpha‐diversity per sample. Amoeba species richness is also known to increase with higher soil moisture content (Romeralo et al ., 2011), but there was not an increase in alpha‐diversity of amoeba microbiomes with higher soil moisture content.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, if there is a corresponding increase in the genetic diversity within a particular amoeba species as pH approaches neutral, then because amoeba samples were collected by pooling multiple individual fruiting bodies, these more genetically diverse amoebae may carry different bacteria leading to an increase in alpha‐diversity per sample. Amoeba species richness is also known to increase with higher soil moisture content (Romeralo et al ., 2011), but there was not an increase in alpha‐diversity of amoeba microbiomes with higher soil moisture content.…”
Section: Discussionmentioning
confidence: 95%
“…An alternative explanation is that amoeba microbiome alpha‐diversity increased as pH approached neutral because the genetic diversity of the amoebae hosts increased. Amoeba species richness is highest at a neutral soil pH, which may itself be due to the availability of more diverse bacterial food (Romeralo et al ., 2011). However, if there is a corresponding increase in the genetic diversity within a particular amoeba species as pH approaches neutral, then because amoeba samples were collected by pooling multiple individual fruiting bodies, these more genetically diverse amoebae may carry different bacteria leading to an increase in alpha‐diversity per sample.…”
Section: Discussionmentioning
confidence: 99%
“…Dictyostelids are abundant in temperate woodland soils but they have also been identified in diverse habitats that include caves, agricultural land, prairies, marshes, sandy mesas, tundra, and tropical forest (e.g., Cavender 1973, 2013; Cavender et al 2002; Landolt et al 2008; Romeralo et al 2010, 2011b; Swanson et al 2001, 2002; Vadell et al 2011). In most cases they are found in association with decaying leaves and organic waste (solid surfaces).…”
Section: Introductionmentioning
confidence: 99%
“…This experiment showed that dictyostelids are affected by environmental factors, especially moisture 6 . It is now known that there are a number of factors which can affect the distribution and abundance of dictyostelids, including the physiographic regime sampled 7,8 , soil pH, soil type, climatic conditions, forest type 6,9,10 , elevation 7,1012 , and latitude 13 . Some species of dictyostelids have been grouped into abundance categories, including very common, common, rare, and very rare 9,14–16 .…”
Section: Introductionmentioning
confidence: 81%
“…to be prominent in drier vegetation types. In the Iberian Peninsula, dictyostelids abundance was reported to be highest in colder and wetter environments, which suggests that this group favors relatively cold places with high levels of water availability 6 .…”
Section: Introductionmentioning
confidence: 99%